Microbiome-derived secondary bile acids promote repair of colonic mucosa after injury - Brecht Attema; Folkert Kuipers (EMBO Molecular Medicine)
Dysbiosis, i.e., an imbalance in the composition of the intestinal microbiome, has been linked to the etiology of inflammatory bowel diseases (IBD). Secondary bile acids (BAs) are microbiome-derived metabolites increasingly recognized for their important signaling functions in host (patho)physiology. In this issue of EMBO Molecular Medicine, Jalil et al (Jalil et al, 2025) report that increased production of secondary BAs upon administration of the human bacterium Clostridium scindens (C. scindens) improves colonic health in mice with chemically-induced colitis via activation of the membrane bound BA receptor TGR5. These findings indicate an important role for secondary BA signaling in colon mucosal healing upon injury and suggest that modulation of microbiome composition could serve as a therapeutic approach for patients with IBD.